Social protection of orphan children and children relating to parent's fighting as a national security complex of the state - Evdokimenko, T. (Київський національний університет імені Тараса Шевченка, 2018)
The article analyzes the reasons for the abolition and implementation of state policy in the field of social protection of children and children deprived of parental authority. Social protection is one of the functions of the state. The main objective of social protection for children and children left without parental care is to create conditions for physical, mental and spiritual development.

У статті проаналізовано причини відмови та реалізації держави політика в Україні щодо соціального захисту дітей-сиріт та дітей, позбавлених повноважень батьківської опіки. Соціальний захист є однією з функцій держави. Головна мета соціального захист дітей-сиріт та дітей, які залишилися без піклування батьків, - це створення умови для фізичного, розумового та духовного розвитку.
СОЦІАЛЬНИЙ ЗАХИСТ ДІТЕЙ-СИРІТ ТА ДІТЕЙ, ПОЗБАВЛЕНИХ БАТЬКІВСЬКОГО ПІКЛУВАННЯ ЯК СКЛАДОВА НАЦІОНАЛЬНОЇ БЕЗПЕКИ ДЕРЖАВИ
Keywords: national security; social security; social protection of orphans and children deprived of parental care; національна безпека; соціальна безпека; соціальний захист дітей-сиріт та дітей; позбавлених батьківського піклування